2016 IEEE International Conference on Multimedia &Amp; Expo Workshops (ICMEW) 2016
DOI: 10.1109/icmew.2016.7574667
|View full text |Cite
|
Sign up to set email alerts
|

HEVC-based light field image coding with bi-predicted self-similarity compensation

Abstract: HEVC-based light field image coding with bi-predicted self-similarity compensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 8 publications
0
60
0
Order By: Relevance
“…In [4] authors suggested to use HEVC Intra Profile to code the lenslet structure, and to improve its performance by integrating self-similarity compensated prediction and estimation. The proposed solution exploits the correlation between neighbooring micro-images in the lenslet image.…”
Section: Introductionmentioning
confidence: 99%
“…In [4] authors suggested to use HEVC Intra Profile to code the lenslet structure, and to improve its performance by integrating self-similarity compensated prediction and estimation. The proposed solution exploits the correlation between neighbooring micro-images in the lenslet image.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial prediction modes have thus been proposed for unfocused cameras in [15] and [42] based on a concept of self-similarity compensated prediction or using locally linear embedding techniques in [43]. These selfsimilarity prediction modes have been further extended to bidirectional prediction in [18] and [19]. The authors in [16] introduce a bi-directional spatial prediction mode in HEVC for encoding elemental images captured by a focused 2.0 camera [44] which has been further extended in [20]) for unfocused 1.0 cameras.…”
Section: B Light Fields Compressionmentioning
confidence: 99%
“…The proposed techniques mostly focus on the compression multi-views and multi-focus from sub-aperture images derived from LF data [7]. A recent improvement is a self-similarity compensated prediction based HEVC coding solution for LF [8]. The key idea is to use bi-prediction of the blocks in a search window with similar information from the LF image.…”
Section: Introductionmentioning
confidence: 99%